IMPLEMENTATION OF DECISION TREE FOR STUDENT DATA PROCESSING - Lestari Ramadewi (INFOKUM, 2021)
SD Negeri 106184 Sekip is one of the public elementary schools in Lubuk Pakam, Deli Serdang Regency. The graduation rate is one of the main problems in an elementary school. The higher the graduation rate of students at an educational institution, the more it will raise the popularity of the school. Likewise, if there is a decrease in the graduation rate, the school will experience a decline in popularity, thus allowing a decrease in applicants / prospective students to enter the school in the following years. This of course raises concerns on the school side. Data mining is intended to provide a solution so that the school knows the most dominant factors affecting the graduation rate. For this reason, the authors are interested in raising this problem into a thesis research entitled "Application of Data Mining for student data processing using the Decision Tree Study Case SDN 106184 Sekip method". The purpose of this study was to determine which factors were most dominant in influencing a student's passing rate, so that in the future, it is hoped that the school will be able to increase student graduation rates in the following years.